2003
DOI: 10.1002/gene.10176
|View full text |Cite
|
Sign up to set email alerts
|

Colocalization of WT1 and cell proliferation reveals conserved mechanisms in temperature‐dependent sex determination

Abstract: SummaryDuring vertebrate development the gonad has two possible fates, the testis or the ovary. The choice between these fates is made by a variety of sex-determining mechanisms, from the sexdetermining gene on the Y chromosome (Sry) in mammals, to nongenetic temperature-dependent systems in many reptiles. Despite the differences in the mechanisms at the top of the sexdetermining cascade, the resulting morphology and many genes involved in early testis and ovarian development are common to most vertebrates, le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 45 publications
(54 reference statements)
0
17
0
Order By: Relevance
“…In mouse, proliferation of Sertoli cell precursors is an essential process that must be initiated to direct the gonad to the male pathway (Schmahl et al, 2000). We found that proliferation of Sertoli cell precursors is also an underlying mechanism of the early size increase of male gonads in T. scripta (Schmahl et al, 2003). We have also identified two other cellular mechanisms that contribute to the organization of the testis in mouse:…”
Section: Introductionmentioning
confidence: 79%
“…In mouse, proliferation of Sertoli cell precursors is an essential process that must be initiated to direct the gonad to the male pathway (Schmahl et al, 2000). We found that proliferation of Sertoli cell precursors is also an underlying mechanism of the early size increase of male gonads in T. scripta (Schmahl et al, 2003). We have also identified two other cellular mechanisms that contribute to the organization of the testis in mouse:…”
Section: Introductionmentioning
confidence: 79%
“…Its role in sex determination and downstream effects therein are unclear. However, studies in humans, mice, and red-eared slider turtles have revealed WT1 as a vital male-specific gene [26]. In addition, mutated WT1 genes in humans and mice have demonstrated XY sex reversal [27].…”
Section: Discussionmentioning
confidence: 97%
“…For example, proliferation of somatic cells is rapidly up-regulated soon after Sry expression begins (82,83). An increase in proliferation is also seen in turtle gonads at the male producing temperature (84), and, in fact, is associated with the male pathway in all species examined so far (85).…”
Section: Sex Determination At the Cellular Levelmentioning
confidence: 72%